Dampak Negatif Adiksi Sosmed Terhadap Motivasi Belajar Pada Siswa Kelas VIII MTS YPPS Sukamiskin - Indira Aristianti; Resti Okta Sari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The growth in social media use among students has raised concerns about its impact on learning motivation. The interest in investigating the influence of social media addiction on students' learning motivation is the main thrust in the educational context. This research aims to identify and analyze the negative impact of social media addiction on students' learning motivation, with a focus on changes in behavior and academic performance. Using a qualitative approach through in-depth case studies of students, data collection was carried out through surveys. Research findings show that social media addiction has a negative impact on students' learning motivation, reflected in decreased concentration, quality of work, and active participation in academic activities. From the results, it is concluded that social media addiction has a significant negative impact on student learning motivation, highlighting the importance of awareness and intervention to reduce this negative impact in the educational environment.